Shorebird Community and Guild in Trisik Beach, Yogyakarta: KOMUNITAS DAN GUILD BURUNG PANTAI DI KAWASAN PANTAI TRISIK, YOGYAKARTA - Sumartono, Nova Ika Rakhmawati; Hernowo, Jarwadi Budi; Santoso, Nyoto (Media Konservasi, 2019)
Trisik Beach is a wetland area located in the southern part of Daerah Istimewa Yogyakarta. Then beach played an important role as shorebirds habitat. The purpose of this study was to analyze the community and food guild for bird communities in the Trisik Beach. This research was conducted in October 2018 - January 2019 using a point count technique. The shorebird community in the Trisik Beach consisted of 22 species which was divided into migratory and residents bird. Guild type of shorebird communities in this area were categorizes into three grup namely mollucivore, insectivore and omnivore. Based on how to get food, Mollucivore guild type food developed into some guild types. The insectivore guild type consisted of one guild type. The Omnivore guild type was developed into ten types. The most commonly found guild type was the omnivore guild type consisted 17 spesies (77%). Keywords: bird community, guild, shorebird, species richness